1H-NMR based metabolic study of MMTV-PyMT mice along with pathological progress to screen biomarkers for the early diagnosis of breast cancer. (17th December 2021) - Liu, Ying; Qi, Cuiling; Zheng, Lingyun; Li, Jiangchao; Wang, Lijing; Yang, Yongxia
Abstract : This study showed the common metabolic changes between BC patients and mice, which were related to pathological processes. Abstract : A 1 H NMR-based metabonomic approach was applied to monitor the alterations of serum metabolic profiles in MMTV-PyMT transgenic mice to detect the dynamic changes associated with the pathological process and explore the early-stage biomarkers. The 1 H NMR spectra of sera samples from four different stages in MMTV-PyMT mice including hyperplasia, adenoma, early carcinoma and late carcinoma stages were recorded and analyzed using multivariate statistical techniques. The results showed that the increased levels of lipid and lactate, and decreased leucine/isoleucine, valine, methionine, glutamine, creatine, PC/GPC, taurine and glucose were of significance for the early carcinoma stage. As the disease progressed (late carcinoma stage), the metabolic profiles changed significantly; some were negatively regulated compared with those at the early carcinoma stage, such as lipid, leucine/isoleucine, methionine and creatine, accompanied by other new metabolite changes of alanine, pyruvate, glutamate, citrate, aspartate, myo-inositol, 3-methylhistidine and formate. It is important to note that breast cancer patients and the early carcinoma stage of MMTV-PyMT mice had some similar metabolite changes, including lipid, lactate, glutamine, creatine, taurine and glucose, which were determined to be of great value for the early clinical diagnosis of breast cancer. The findings from this study provided valuable biomarkers for the early clinical diagnosis of breast cancer, and showed the potential power of integrating NMR techniques and pattern recognition methods for the analysis of the biochemical changes under certain pathophysiological conditions.